Recognizing same and different [kit]. - Jenkins, Emily, 1967- (What's the big idea?., 2006)
The goals of this kit are to observe, describe and compare sizes, shapes, quantities, colors and functions; to notice similarities and differences and put objects into groups based on shared attributes; to recognize and establish attributes (criteria) for selecting objects to be classified on the basis of sameness and difference; to discover the many ways objects can be described and sorted according to physical characteristics and structure; and to use and/or function.